Positive electrode material and preparation method and application thereof
Through the introduction of the carbon -covered layer surface of the positive active substrate, the parental base group is introduced to solve the problem of poor infiltration of battery pole sheets, and a higher electrolyte infiltration, low internal resistance and high energy efficiency are achieved.
Patent Information
- Application Number
- CN202411364641.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-27
AI Technical Summary
In the prior art, the wetting properties of the battery electrode sheet are poor, resulting in losses in the energy efficiency and capacity of the battery cell. Especially when the battery cycle increases, insufficient electrolyte in the diaphragm pores cannot effectively wet the electrode sheet.
A new cathode material is formed by introducing lipophilic groups on the surface of the carbon coating layer of the cathode active substrate. The ester-philic group is chemically bonded to the surface of the carbon coating through covalent bonds, which improves the wettability of the cathode material to the ester electrolyte.
It significantly enhances the infiltration of the positive active material to the electrolyte, reduces the internal resistance of the battery, improves energy efficiency, and ensures the electrochemical properties of positive active materials.
Smart Images

Figure CN118867212B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage materials, and in particular to a positive electrode material and a preparation method and application thereof. Background Art
[0002] For lithium-ion batteries, materials, structural design and manufacturing level all affect their performance. Among them, the wetting of lithium-ion battery pole pieces is an issue that cannot be ignored in the design and manufacturing process of lithium batteries. Whether the pole piece is wetted or not will directly determine the performance of the electrode active material. Poles with low wettability often show high internal resistance, resulting in loss of battery cell energy efficiency and capacity. Therefore, ensuring sufficient wetting of battery pole pieces has a significant effect on improving the performance of lithium batteries. In order to ensure sufficient wetting of battery pole pieces, in addition to extending the wetting time during the manufacturing process, it is more important to improve the wetting ability of battery materials in the electrolyte. The current focus is mainly on diaphragm and pole piece design.
[0003] The diaphragm is an important material to ensure the wettability of the electrode. The porosity of the diaphragm and its wettability to the electrolyte will affect its ability to absorb liquid. At present, the main way to improve the wettability of the diaphragm is to increase its porosity through diaphragm structure design, or to improve its wettability to the electrolyte through surface modification of the diaphragm, so as to achieve the purpose of improving its absorption speed and absorption capacity.
[0004] In addition, the diffusion of lithium ions in the material is currently improved through the design of the pole piece structure, that is, the filling rate of the electrolyte in the pole piece is improved. The main method is to design a multilayer structure with different porosities to ensure the diffusion rate of lithium ions in the pole piece. For example, a layer of coating with lower porosity is first applied on the side close to the current collector, and then a layer of coating with higher porosity is applied on its surface. In this way, the pole piece obtained ensures the energy density while improving the diffusion of lithium ions in the pole piece.
[0005] Although the methods of improving the wettability of the electrode by designing the diaphragm and the electrode structure can achieve good results, these strategies are all passive ways to improve the wetting effect of the electrode material. When the battery is cycled and the electrolyte is consumed to a certain extent, this method cannot achieve a good wetting effect. At this time, although the pores of the diaphragm are filled with a certain amount of electrolyte, the amount is not enough to wet the electrode well. Summary of the invention
[0006] The main purpose of the present invention is to provide a positive electrode material and a preparation method and application thereof, so as to solve the problem of poor wettability of battery pole pieces in the prior art.
[0007] In order to achieve the above object, according to one aspect of the present invention, a positive electrode material is provided, the positive electrode material comprises a positive electrode active substrate, the surface of the positive electrode active substrate is coated with a carbon coating layer;
[0008] The surface of the carbon coating layer has lipophilic groups.
[0009] Furthermore, the lipophilic group is a C2~C8 carbonyl-containing group.
[0010] Further, the structural formula of the lipophilic group is:
[0011] Formula I;
[0012] Wherein, in Formula I, R1 is a C1~C4 alkylene group, and R2 is a C1~C4 alkyl group or an amino group.
[0013] The "*" in Formula I of the present invention is a chemical group connection site.
[0014] Furthermore, R1 is a methylene group or an ethylene group, and / or R2 is a methyl group, an ethyl group or an amino group.
[0015] Furthermore, the lipophilic group is chemically bonded to the surface of the carbon coating layer in the form of a covalent bond.
[0016] Furthermore, the weight proportion of the lipophilic groups in the carbon coating layer is 1-2.5%.
[0017] Furthermore, the weight of the carbon coating layer is 1-2% of the weight of the positive electrode active substrate.
[0018] Furthermore, the positive electrode active substrate includes lithium iron phosphate, lithium iron manganese phosphate, lithium nickel iron phosphate, nickel cobalt manganese or nickel cobalt aluminum material.
[0019] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned positive electrode material, which comprises the following steps:
[0020] Step S1: obtaining a positive electrode active substrate;
[0021] Step S2: performing carbon coating modification on the positive electrode active substrate to obtain a carbon coated positive electrode active substrate;
[0022] Step S3: performing surface modification on the carbon-coated positive electrode active substrate, introducing esterophilic groups on the surface of the carbon coating layer, and forming a positive electrode material.
[0023] Furthermore, the lipophilic group in step S3 is derived from the carbonyl group in the halogenated ketone or the carbonyl group in the halogenated amide.
[0024] Furthermore, in step S3, the process of surface modification of the carbon-coated positive electrode active substrate includes:
[0025] Step S3-1: obtaining a carbon-coated positive electrode active substrate with a hydroxylated surface;
[0026] Step S3-2: mixing the surface hydroxylated carbon-coated positive electrode active substrate, the alkaline substance and the solvent in an inert atmosphere, and heating the mixture for reaction to obtain an intermediate;
[0027] Step S3-3: mixing the intermediate and the compound containing the lipophilic group in an inert atmosphere, heating and reacting, and obtaining a carbon-coated positive electrode active substrate having the lipophilic group on the surface, i.e., a positive electrode material;
[0028] Wherein, the compound containing the esterophilic group is a halogenated ketone or a halogenated amide;
[0029] The halogenated ketone has the structure shown in Formula II:
[0030] Formula II;
[0031] In formula II, R1 is a C1-C4 alkylene group, X is a halogen atom, and R2 is a C1-C4 alkyl group;
[0032] Further, R1 is methylene or ethylene, and / or, R2 is methyl or ethyl;
[0033] The halogenated amide has the structure shown in Formula III:
[0034] Formula III;
[0035] In formula III, R1 is a C1-C4 alkylene group, and X is a halogen atom;
[0036] Furthermore, R1 is a methylene group or an ethylene group.
[0037] Furthermore, in step S3-2, the alkaline substance includes one or more of sodium hydride, potassium hydride, lithium diisopropylamide and lithium bis(trimethylsilyl)amide.
[0038] Further, the solvent includes N,N-dimethylformamide.
[0039] Further, the inert atmosphere includes an argon atmosphere.
[0040] Furthermore, the weight ratio of the alkaline substance to the surface hydroxylated carbon-coated positive electrode active substrate is (0.05~0.2):1.
[0041] Furthermore, the weight ratio of the alkaline substance to the surface hydroxylated carbon-coated positive electrode active substrate is (0.1~0.2):1.
[0042] Furthermore, the conditions for the heating reaction in step S3-2 include: temperature of 30-50°C and time of 3.5-4.5h.
[0043] Furthermore, in step S3-3, the halogenated ketone is selected from one or more of chloroacetone, chlorobutyl ketone, bromoacetone, bromobutyl ketone and iodoacetone.
[0044] Furthermore, in step S3-3, the halogenated ketone is selected from chloroacetone, chlorobutanone or bromoacetone.
[0045] Furthermore, in step S3-3, the halogenated amide is selected from at least one of chloroacetamide, 3-chloropropionamide, and chlorobutanamide.
[0046] Furthermore, in step S3-3, the halogenated amide is selected from chloroacetamide or 3-chloropropionamide.
[0047] Furthermore, the weight ratio of the alkaline substance, the surface hydroxylated carbon-coated positive electrode active substrate and the compound containing the esterophilic group is (0.05~0.2):1:(0.4~0.6).
[0048] Furthermore, the weight ratio of the alkaline substance, the surface hydroxylated carbon-coated positive electrode active substrate and the compound containing the esterophilic group is (0.1~0.2):1:(0.4~0.6).
[0049] Furthermore, the conditions for the heating reaction in step S3-3 include: a reaction temperature of 55°C to 65°C and a reaction time of 10 to 18 hours.
[0050] Further, in step S3-3, the product after the heating reaction is cooled to 20°C~35°C and aged for 1~2h to obtain a crude product. The crude product is filtered, washed with water and spray granulated in sequence to obtain a carbon-coated positive electrode active substrate having lipophilic groups on the surface, i.e., a positive electrode material.
[0051] Furthermore, in step S3-1, the preparation process of the surface hydroxylated carbon-coated positive electrode active substrate includes: mixing the carbon-coated positive electrode active substrate and an alkali solution, heating the mixture for reaction, and obtaining the surface hydroxylated carbon-coated positive electrode active substrate.
[0052] Furthermore, the ratio of the carbon-coated positive electrode active substrate to the alkaline solution is (20~30) g:100 mL, and the concentration of the alkaline solution is 1.5~2.5 mol / L.
[0053] Furthermore, the alkali solution is selected from one or more of a sodium hydroxide solution, a potassium hydroxide solution and a lithium hydroxide solution.
[0054] Furthermore, the conditions for the heating reaction in step S3-1 include: a temperature of 180°C to 220°C and a time of 5.5 to 6.5 hours.
[0055] Furthermore, in step S1, the positive electrode active substrate includes lithium iron phosphate, lithium iron manganese phosphate, lithium nickel iron phosphate, nickel cobalt manganese or nickel cobalt aluminum.
[0056] Furthermore, in step S2, the carbon source for carbon coating modification includes one or more of glucose, sucrose, citric acid, polystyrene and biomass materials.
[0057] Furthermore, in step S2, the process of carbon-coating and modifying the positive electrode active substrate includes: mixing the positive electrode active substrate and a carbon source, and calcining them in an inert atmosphere to obtain a carbon-coated positive electrode active substrate.
[0058] Furthermore, the weight ratio of the positive electrode active substrate to the carbon source is 1:(1~1.2).
[0059] Further, the inert atmosphere includes an argon atmosphere.
[0060] Furthermore, the calcination conditions include: a temperature of 550° C. to 650° C. and a time of 5.5 to 6.5 hours.
[0061] According to a third aspect of the present invention, a positive electrode plate is provided, which includes a foil and a positive electrode slurry coated on the surface of the foil; the positive electrode slurry includes a positive electrode material; the positive electrode material is the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned method.
[0062] According to a third aspect of the present invention, a battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the positive electrode sheet is the above-mentioned positive electrode sheet.
[0063] Further, the electrolyte includes an ester solvent, further a carbonate solvent, more specifically one or more of dimethyl carbonate, ethylene carbonate, methyl ethyl carbonate and diethyl carbonate.
[0064] The technical solution of the present invention provides a positive electrode material for a battery. While coating lithium iron phosphate with carbon, the surface energy of the carbon coating layer is changed by introducing ester-philic carbonyl groups, which significantly improves the wettability of the positive electrode active particles to the electrolyte. At the same time, the method does not change the bulk structure of the active material, thus ensuring the electrochemical performance of the positive electrode active material. The positive electrode sheet prepared by the present invention exhibits excellent electrolyte wettability, and the prepared battery exhibits characteristics such as low internal resistance and high energy efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0066] Figure 1 A liquid absorption curve of the positive electrode material prepared with different strong base ratios in the embodiment of the present invention is shown;
[0067] Figure 2A liquid absorption curve of positive electrode materials prepared from different halides according to an embodiment of the present invention is shown;
[0068] Figure 3 Shows the charge and discharge energy efficiency test diagram of the battery cells of various embodiments of the present invention and comparative examples;
[0069] Figure 4 The DCR internal resistance test diagram during the charging process of each embodiment of the present invention and the comparative example is shown;
[0070] Figure 5 The DCR internal resistance test diagrams during the discharge process of various embodiments of the present invention and comparative examples are shown. DETAILED DESCRIPTION
[0071] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0072] In order to improve the wettability of the battery positive electrode sheet in the electrolyte, the present invention improves the structure of the positive electrode material. The positive electrode material includes a positive electrode active substrate, and the surface of the positive electrode active substrate is coated with a carbon coating layer; wherein the surface of the carbon coating layer has esterophilic groups.
[0073] The above-mentioned lipophilic group refers to a group having a polarity close to that of an ester solvent and having a strong affinity.
[0074] The present invention takes the molecular structure of the positive electrode active material into consideration, and by attaching lipophilic groups to the surface of the carbon coating material, the surface energy of the carbon coating is greatly changed, and the wettability of the positive electrode active substrate itself to the ester electrolyte is effectively improved, thereby reducing the internal resistance of the battery and the risk of cycle diving. At the same time, it can ensure that the positive electrode active substrate itself has good electrochemical properties, and enhance the active adsorption and infiltration ability of the positive electrode active material itself to the electrolyte, fundamentally solving the problem of battery positive electrode sheet and electrolyte infiltration.
[0075] The present invention conducts research from the perspective of the polarity of ester electrolyte solvents and finds that when the lipophilic group introduced on the carbon layer of the positive electrode material is a carbonyl group, better wettability can be obtained between the positive electrode active material and the ester electrolyte solvent; for example, when the lipophilic group is a carbonyl-containing group of C2~C8, there is a better wetting effect between the positive electrode material and the ester electrolyte, and the electrochemical properties of the positive electrode material itself will not be destroyed.
[0076] The present invention expresses the chemical structure of the lipophilic group through formula I:
[0077] Formula I.
[0078] The present invention finds that the length of the carbon chain in the above-mentioned lipophilic group will affect the difficulty and effect of connecting it to the carbon coating layer. The longer the carbon chain, the more difficult it is to connect the lipophilic group to the carbon coating layer. Therefore, R1 in Formula I of the present invention is selected from C1~C4 alkylene, and R2 is selected from C1~C4 alkyl or amino; adopting the above design can not only maximize the wettability of the positive electrode material in the ester electrolyte, but also ensure that the positive electrode material does not absorb excessive water, and can also ensure the electrochemical performance of the positive electrode material itself, and is also more conducive to the introduction of the lipophilic group into the carbon coating layer.
[0079] As a specific embodiment, R1 in the lipophilic group of the present invention can be selected as methylene or ethylene, and / or R2 can be selected as methyl, ethyl or amino; by taking into account wettability, low water absorption, electrochemical performance and ease of introduction, R1 and R2 can be limited to other lipophilic groups that meet the above introduction conditions or can bring about the above effects. Selecting the above R1 and R2 groups, the corresponding lipophilic groups can better take into account the above performance aspects.
[0080] More specifically, the lipophilic groups selected by the present invention are chemically bonded to the surface of the carbon coating layer in the form of covalent bonds; that is, the present invention uses a chemical reaction to connect the lipophilic groups to the surface of the carbon coating layer, and the lipophilic substances and the carbon-coated positive electrode substrate form an integral material, which can make the positive electrode material structure stable, have a long service life, and have a stable wetting effect.
[0081] Since the lipophilic groups and ester electrolyte solvents have similar polarities in structure, the two have good compatibility and wettability. The weight proportion of the lipophilic groups in the carbon coating layer affects the wetting effect with the ester solvent; for example, when the content of the lipophilic groups is 1~2.5%, it has good wettability.
[0082] In order to ensure the electrochemical performance of the positive electrode material and the effect of introducing esterophilic groups into the carbon coating layer in the later stage and the influence on wettability, the weight of the carbon coating layer in the positive electrode material of the present invention is 1-2% of the weight of the positive electrode active substrate.
[0083] The present invention mainly introduces lipophilic groups into the carbon coating layer to improve the wettability of the positive electrode material and ester solvents. This method is applicable to more positive electrode active substrates, such as lithium iron phosphate, lithium iron manganese phosphate, lithium nickel iron phosphate, nickel cobalt manganese or nickel cobalt aluminum materials, and can also be other positive electrode active substrates that can be carbon-coated.
[0084] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned positive electrode material, which comprises the following steps:
[0085] Step S1: obtaining a positive electrode active substrate;
[0086] Step S2: performing carbon coating modification on the positive electrode active substrate to obtain a carbon coated positive electrode active substrate;
[0087] Step S3: performing surface modification on the carbon-coated positive electrode active substrate, introducing esterophilic groups on the surface of the carbon coating layer, and forming a positive electrode material.
[0088] In order to improve the wettability of the positive electrode material lithium iron phosphate to the electrolyte, reduce the internal resistance of the lithium-ion battery, and improve the battery energy efficiency, the present invention, while coating the positive electrode active substrate with carbon, introduces ester-philic carbonyl groups with a polarity close to that of the electrolyte, changes the surface energy of the carbon coating layer, and significantly improves the wettability of the positive electrode active material to the electrolyte. At the same time, the method does not change the bulk structure of the positive electrode active material, thus ensuring the electrochemical performance of the positive electrode active material. The positive electrode sheet prepared by this method exhibits excellent electrolyte wettability, and the prepared battery exhibits characteristics such as low internal resistance and high energy efficiency.
[0089] As described above, after the lipophilic group introduced into the carbon coating layer of the positive electrode material in the present invention is a carbonyl group, better wettability can be achieved between the positive electrode active material and the ester electrolyte solvent; the lipophilic group selected by the present invention mainly comes from the carbonyl group in the halogenated ketone or the carbonyl group in the halogenated amide. These two compounds are more suitable for connection to the carbon coating layer and have better wettability to the ester solvent. They will not be adversely affected by other substances or the environment during the modification process. The molecular structure of these two compounds is relatively stable in the modified system, for example, they will not be decomposed by the chemical environment.
[0090] The technical concept of the present invention for surface modification of carbon-coated positive electrode active substrates is as follows: after preparing the carbon-coated positive electrode material, the carbon coating layer on its surface is firstly hydroxylated. Considering the instability of positive electrode materials such as lithium iron phosphate in an acidic system, an alkaline method is used to hydroxylate the carbon coating layer. After the hydroxylation treatment, in order to successfully connect the carbonyl group to the surface, a strong alkaline substance such as NaH is selected to remove the H in the -OH on the surface of the carbon coating layer. + ions, the hydroxyl group becomes CO - As a nucleophilic reagent, it attacks the R1 carbon cation connected to the halogen atom in the halogenated ketone or halogenated amide. The halogenated ketone or halogenated amide will then lose the halogen atom and connect to the surface of the carbon-coated material, thereby successfully performing esterification modification on the carbon coating. The presence of the carbonyl group on the carbon coating can effectively improve the wettability of positive electrode materials such as lithium iron phosphate to ester electrolytes.
[0091] The reaction process involved in the technical concept of the present invention is as follows:
[0092] (C) n -(OH) n +nNaH→(C)n -(O-Na) n +nH2 (1);
[0093] (2);
[0094] As a specific embodiment of the above technical concept of the present invention, the process of surface modification of the carbon-coated positive electrode active substrate in the method of the present invention includes:
[0095] Step S3-1: obtaining a carbon-coated positive electrode active substrate with a hydroxylated surface;
[0096] Step S3-2: mixing the surface hydroxylated carbon-coated positive electrode active substrate, the alkaline substance and the solvent in an inert atmosphere, and heating the mixture for reaction to obtain an intermediate;
[0097] Step S3-3: mixing the intermediate and the compound containing the lipophilic group in an inert atmosphere, heating and reacting, and obtaining a carbon-coated positive electrode active substrate having the lipophilic group on the surface, i.e., a positive electrode material;
[0098] Wherein, the compound containing the esterophilic group is a halogenated ketone or a halogenated amide;
[0099] The halogenated ketone has the structure shown in Formula II:
[0100] Formula II;
[0101] In formula II, R1 is a C1-C4 alkylene group, X is a halogen atom, and R2 is a C1-C4 alkyl group.
[0102] The present invention considers that the carbon chain length of the lipophilic group selected in the surface modification process may increase the difficulty of the reaction if it is too long, and appropriately limits the carbon chain length to 2-8, for example, R1 can be methylene, ethylene, propylene, butylene, etc., and R2 can be methyl, ethyl, propyl, butyl, etc. Considering the source of raw materials, R1 can be methylene or ethylene, and R2 can be methyl or ethyl; X is a halogen atom, and a chlorine atom, a bromine atom, or an iodine atom can be selected, especially a chlorine atom and a bromine atom.
[0103] The halogenated amide has the structure shown in Formula III:
[0104] Formula III;
[0105] In formula III, R1 is a C1-C4 alkylene group, and X is a halogen atom.
[0106] Similarly, the present invention takes into account that the carbon chain length of the lipophilic group selected in the surface modification process may increase the difficulty of the reaction if it is too long, and appropriately limits the carbon chain length to 2-8. For example, R1 can be a methylene group, an ethylene group, a propylene group, a butylene group, etc., and the original R2 position is an amino group; considering the source of raw materials, R1 can be a methylene group or an ethylene group; X is a halogen atom, and a chlorine atom, a bromine atom, or an iodine atom can be selected, especially a chlorine atom and a bromine atom.
[0107] As a specific implementation manner, in step S3-3, the halogenated ketone is selected from one or more of chloroacetone, chlorobutanone, bromoacetone, bromobutylketone and iodoacetone; chloroacetone, chlorobutanone and bromoacetone can be selected from the source of raw materials; the halogenated amide is selected from chloroacetamide, 3-chloropropionamide or chlorobutanamide, and chloroacetamide or 3-chloropropionamide can be selected from the source of raw materials.
[0108] Specific examples include the following halogenated ketones and halogenated amides:
[0109] .
[0110] As a specific embodiment, in the process of "extracting hydrogen" in step S3-2 of the present invention, the base substance (strong base) selected may be, in addition to sodium hydride (NaH), one or more of potassium hydride, lithium diisopropylamide and lithium bis(trimethylsilyl)amide having similar functions; these strong base substances can be used to remove H from -OH on the carbon coating layer. + ions, the hydroxyl group becomes CO - As a nucleophile, it attacks the R1 carbon cation attached to the halogen atom in the halogenated ketone or halogenated amide.
[0111] As a specific implementation manner, the solvent used in step S3-2 is N,N-dimethylformamide, which is used to dissolve strong alkaline substances such as NaH to facilitate the reaction.
[0112] As a specific implementation, the hydrogen extraction process in step S3-2 is performed under the protection of an inert atmosphere, such as an argon atmosphere.
[0113] As a specific implementation, the weight ratio of the alkaline substance to the surface hydroxylated carbon-coated positive electrode active substrate is (0.05-0.2):1; for example, 0.05:1, 0.1:1, 0.15:1, 0.2:1, etc.; the present invention adopts this reaction ratio to achieve the purpose of "extraction of hydrogen" without destroying the structure of the active material due to strong alkalinity. For example, when the alkaline substance is excessive, the remaining alkaline substance after the reaction will remove hydrogen from the halogenated copper, resulting in a side reaction.
[0114] As a specific implementation, the conditions for the heating reaction in step S3-2 include: a temperature of 30-50°C and a time of 3.5-4.5 h; the "hydrogen extraction" process of the present invention can adopt a medium-low temperature reaction. If the temperature is too high, the controllability of the reaction process is poor.
[0115] As a specific implementation, in step S3-3, the halogenated ketone is selected from one or more of chloroacetone, chlorobutyl ketone, bromoacetone, bromobutyl ketone and iodoacetone; chloroacetone, chlorobutyl ketone and bromoacetone can be selected from the perspective of raw material source.
[0116] As a specific embodiment, the weight ratio of the alkaline substance, the surface hydroxylated carbon-coated positive electrode active substrate and the compound containing the esterophilic group is (0.05~0.2):1:(0.4~0.6); for example, the weight ratio of the alkaline substance and the surface hydroxylated carbon-coated positive electrode active substrate is 0.05:1, 0.08:1, 0.1:1, 0.13:1, 0.15:1, 0.2:1; the weight ratio of the surface hydroxylated carbon-coated positive electrode active substrate and the compound containing the esterophilic group is 1 :0.4, 1:0.45, 1:0.5, 1:0.55, 1:0.6; when the lipophilic compound is in excess, the lipophilic group can be fully introduced; the present invention expresses the ratio between the intermediate of step S3-3 and the compound containing the lipophilic group through the ratio of the alkaline substance, the surface hydroxylated carbon-coated positive electrode active substrate and the compound containing the lipophilic group. By adopting this ratio, the lipophilic group and the intermediate (substance after hydrogen extraction) can be fully connected, and the final positive electrode material can be obtained by first extracting hydrogen and then connecting the lipophilic group.
[0117] As a specific embodiment, the conditions of the heating reaction in step S3-3 include: a reaction temperature of 55 to 65° C. and a reaction time of 10 to 18 hours; the reaction temperature and reaction time can effectively remove the halogen atom from the halogenated ketone or halogenated amide and react with CO - Connection is achieved, thereby achieving the purpose of connecting the lipophilic group to the surface of the carbon material and completing the surface modification; if the temperature is too high, the carbonyl group will participate in the reaction, resulting in side reactions.
[0118] As a specific implementation method, in step S3-3, the product after the heating reaction is cooled to 20~35°C, matured for 1~2h, and the reaction is stopped to obtain a crude product. The crude product is filtered, washed with water and spray granulated in sequence to obtain a carbon-coated positive electrode active substrate with esterophilic groups on the surface, that is, a positive electrode material.
[0119] As a specific implementation, in step S3-1, the surface hydroxylated carbon-coated positive electrode active substrate can be synthesized or selected from the prior art; during synthesis, the preparation process is: mixing the carbon-coated positive electrode active substrate and alkaline solution, heating the reaction, and obtaining the surface hydroxylated carbon-coated positive electrode active substrate.
[0120] As a specific implementation manner, the ratio of the carbon-coated positive electrode active substrate and the alkali solution is (20~30) g: 100 mL, and the concentration of the alkali solution is 1.5~2.5 mol / L; wherein the alkali solution is selected from one or more of sodium hydroxide solution, potassium hydroxide solution and lithium hydroxide solution; the conditions of the hydroxylation heating reaction include: temperature of 180°C~220°C, time of 5.5~6.5h; by using the above raw material ratio, reaction temperature and reaction time, the hydroxylation reaction can be fully carried out without affecting the structure of the active material, thereby obtaining a suitable hydroxylated carbon-coated positive electrode active material.
[0121] The positive electrode active substrate in step S1 of the present invention can be synthesized or purchased from the market, and its type is not limited as long as its surface can be coated with a carbon coating layer.
[0122] As a specific implementation mode, in step S2 of the present invention, the process of carbon-coating and modifying the positive electrode active substrate includes: mixing the positive electrode active substrate and the carbon source, and calcining them in an inert protective atmosphere such as argon to obtain a carbon-coated positive electrode active substrate; the carbon source for the carbon coating modification can be selected from one or more of glucose, sucrose, citric acid, polystyrene and biomass materials; the weight ratio of the positive electrode active substrate to the carbon source is 1: (1~1.2); the calcination temperature is 550℃~650℃, and the time is 5.5~6.5h.
[0123] The present invention can use the above conditions to carry out carbon coating modification on the positive electrode active substrate, and can also use other methods to carry out carbon coating modification or use commercially available carbon-coated modified positive electrode active substrate.
[0124] Based on the positive electrode material developed by the present invention and having good wettability with ester electrolytes, the present invention also provides a positive electrode plate, which includes a foil material and the positive electrode slurry of the present invention coated on the surface of the foil material.
[0125] Based on a positive electrode sheet with good wettability with ester electrolyte developed by the present invention, the present invention also provides a battery, including the positive electrode sheet, negative electrode sheet, separator and electrolyte of the present invention.
[0126] The positive electrode plate and ester electrolyte developed by the present invention have good wettability, such as carbonate solvents, more specifically one or more of dimethyl carbonate, ethylene carbonate, methyl ethyl carbonate and diethyl carbonate.
[0127] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0128] Example 1
[0129] (1) Preparation of modified materials
[0130] 1. Weigh 1 part of lithium iron phosphate precursor iron phosphate, 1.02 parts of lithium source, add appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500rpm for 12h to obtain a mixed slurry with a particle size of 300-1000nm, then use spray granulation to obtain powder, place the powder in a tubular furnace, calcine at 650℃ for 24h in Ar atmosphere to obtain lithium iron phosphate powder, all are measured by weight.
[0131] 2. Take 1 part of lithium iron phosphate powder, add 1.1 parts of glucose, add an appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500 rpm for 4 hours, spray granulate, place in a tubular furnace, and calcine at 700 ° C for 6 hours under Ar atmosphere to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0132] 3. The carbon-coated lithium iron phosphate positive electrode material obtained above is added to a 2M NaOH aqueous solution, stirred thoroughly and then transferred into a reactor, reacted at 200°C for 6 hours, cooled to room temperature after the reaction, filtered, and washed with deionized water and anhydrous ethanol, and finally spray granulated to obtain surface hydroxylated carbon-coated lithium iron phosphate.
[0133] 4. Take an appropriate amount of strong base NaH (0.05 parts) and stir to dissolve in DMF under Ar protection, add an appropriate amount of hydroxylated carbon-coated lithium iron phosphate powder (1 part), stir and react at 40°C for 4 hours, then raise the temperature to 60°C, add an appropriate amount of chloroacetone (0.5 parts) and react for 12 hours, cool to room temperature and mature for 1 hour to stop the reaction, filter the reactant, and wash it repeatedly with deionized water and anhydrous ethanol, and finally use spray granulation to obtain a carbon-coated lithium iron phosphate positive electrode material with carbonyl groups on the surface.
[0134] (2) Electrode preparation
[0135] The slurry was prepared according to the ratio of lithium iron phosphate positive electrode material: conductive agent: CNT: binder: NMP solvent of 96.8:0.8:0.4:2:60.
[0136] The specific process is: put the lithium iron phosphate positive electrode material, binder and conductive agent in the above proportion into a stirring tank, dry mix and stir for 30 minutes at an orbital speed of 15rpm and a dispersion speed of 400rpm, then add 60% of the above NMP solvent for kneading and stirring, the stirring orbital speed is 15rpm, the dispersion speed is 400rpm, and the stirring time is 40min; then add the remaining amount of NMP solvent, stir for 60 minutes at an orbital speed of 22rpm and a dispersion speed of 1000rpm; finally, add the above amount of CNT, stir for 120 minutes at an orbital speed and a dispersion speed of 1000rpm to obtain a positive electrode slurry.
[0137] The positive electrode slurry prepared above is coated on the carbon-coated aluminum foil as required to obtain the positive electrode sheet of Example 1.
[0138] Weigh the negative electrode slurry raw materials according to the following weight parts: 96 parts of graphite powder (negative electrode active material), 0.8 parts of SP (conductive agent), 2 parts of SBR (binder), 1.2 parts of CMC (dispersant), and 90 parts of deionized water;
[0139] The above amount of graphite powder, conductive agent and dispersant are put into a mixing tank and dry mixed for 30 minutes, with a stirring revolution speed of 15 rpm and a dispersion speed of 500 rpm. Thereafter, 50 parts of deionized water are added for kneading and stirring for 60 min, with a stirring revolution speed of 20 rpm and a dispersion speed of 300 rpm. Then, the remaining deionized water is added for high-speed dispersion, with a stirring revolution speed of 22 rpm and a dispersion speed of 1000 rpm. Finally, a binder is added and stirred for 30 minutes, with a stirring revolution speed of 22 rpm and a dispersion speed of 500 rpm, to finally obtain a negative electrode slurry; after the prepared negative electrode slurry is coated on copper foil, a negative electrode sheet is obtained.
[0140] (3) The positive electrode sheet and the negative electrode sheet obtained in Example 1 were assembled by a stacking method to obtain a soft-pack battery cell. The separator used for assembly was a 7+2+2 thick coated PP separator. The amount of electrolyte used for a single battery cell was 10 g. The specific ratio was DMC:EC=1:1. The solubility of the lithium salt LiPF6 was 1 mol / L. The nominal capacity of the obtained soft-pack battery cell was 2.3 Ah.
[0141] Example 2
[0142] (1) Preparation of modified materials
[0143] S1: Weigh 1 part of lithium iron phosphate precursor iron phosphate, 1.02 parts of lithium source, add appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500rpm for 12h to obtain a mixed slurry with a particle size of 300-1000nm, then use spray granulation to obtain powder, place the powder in a tubular furnace, and calcine at 650℃ for 24h in Ar atmosphere to obtain lithium iron phosphate powder. All are measured by weight.
[0144] S2: Take 1 part of lithium iron phosphate powder, add 1.1 parts of glucose, add an appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500 rpm for 4 hours, spray granulate, place in a tubular furnace, and calcine at 700°C for 6 hours under Ar atmosphere to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0145] S3: Add the carbon-coated lithium iron phosphate positive electrode material obtained above to a 2M NaOH aqueous solution, stir it thoroughly and then transfer it into a reactor, react at 200°C for 6 hours, cool it to room temperature after the reaction, filter it, and wash it with deionized water and anhydrous ethanol. Finally, spray granulation is used to obtain the surface hydroxylated carbon-coated lithium iron phosphate.
[0146] S4: Take an appropriate amount of sodium hydride (0.1 parts) and stir to dissolve in DMF under Ar protection, add an appropriate amount of hydroxylated carbon-coated lithium iron phosphate powder (1 part), stir and react at 40°C for 4 hours, then raise the temperature to 60°C, add an appropriate amount of chloroacetone (0.5 parts) and react for 12 hours, cool to room temperature and mature for 1 hour, stop the reaction, filter the reactant, and wash it repeatedly with deionized water and anhydrous ethanol, and finally use spray granulation to obtain a carbon-coated lithium iron phosphate positive electrode material with carbonyl groups on the surface.
[0147] (2) Electrode preparation
[0148] According to specific requirements, the positive electrode sheet and the negative electrode sheet of Example 2 are prepared according to the electrode sheet preparation method and process of Example 1.
[0149] (3) The positive electrode sheet and the negative electrode sheet obtained in Example 2 were assembled into a soft-pack battery cell according to the method of Example 1. The resulting soft-pack battery cell had a nominal capacity of 2.3 Ah.
[0150] Example 3
[0151] (1) Preparation of modified materials
[0152] S1: Weigh 1 part of lithium iron phosphate precursor iron phosphate and 1.02 parts of lithium source, add appropriate amount (2-3 parts) of anhydrous ethanol, and ball mill at 500rpm for 12h to obtain a mixed slurry with a particle size of 300-1000nm, then use spray granulation to obtain powder, place the powder in a tubular furnace, and calcine at 650℃ for 24h in Ar atmosphere to obtain lithium iron phosphate powder.
[0153] S2: Take 1 part of lithium iron phosphate powder, add 1.1 parts of glucose, add an appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500 rpm for 4 hours, spray granulate, place in a tubular furnace, and calcine at 700°C for 6 hours under Ar atmosphere to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0154] S3: Add the carbon-coated lithium iron phosphate positive electrode material obtained above to a 2M NaOH aqueous solution, stir it thoroughly and then transfer it into a reactor, react at 200°C for 6 hours, cool it to room temperature after the reaction, filter it, and wash it with deionized water and anhydrous ethanol. Finally, spray granulation is used to obtain the surface hydroxylated carbon-coated lithium iron phosphate.
[0155] S3: Take an appropriate amount of sodium hydride (0.15 parts) and stir to dissolve in DMF under Ar protection, add an appropriate amount of hydroxylated carbon-coated lithium iron phosphate powder (1 part), stir and react at 40°C for 4 hours, then raise the temperature to 60°C, add an appropriate amount of chloroacetone (0.5 parts) and react for 12 hours, cool to room temperature and mature for 1 hour, stop the reaction, filter the reactant, and wash it repeatedly with deionized water and anhydrous ethanol, and finally use spray granulation to obtain a carbon-coated lithium iron phosphate positive electrode material with carbonyl groups on the surface.
[0156] (2) Electrode preparation
[0157] According to specific requirements, the positive electrode sheet and the negative electrode sheet of Example 3 are prepared according to the electrode sheet preparation method and process of Example 1.
[0158] (3) The positive electrode sheet and the negative electrode sheet obtained in Example 3 were assembled into a soft-pack battery cell according to the method of Example 1. The resulting soft-pack battery cell had a nominal capacity of 2.3 Ah.
[0159] Example 4
[0160] (1) Preparation of modified materials
[0161] S1: Weigh 1 part of lithium iron phosphate precursor iron phosphate and 1.02 parts of lithium source, add appropriate amount (2-3 parts) of anhydrous ethanol, and ball mill at 500rpm for 12h to obtain a mixed slurry with a particle size of 300-1000nm, then use spray granulation to obtain powder, place the powder in a tubular furnace, and calcine at 650℃ for 24h in Ar atmosphere to obtain lithium iron phosphate powder.
[0162] S2: Take 1 part of lithium iron phosphate powder, add 1.1 parts of glucose, add an appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500 rpm for 4 hours, spray granulate, place in a tubular furnace, and calcine at 700°C for 6 hours under Ar atmosphere to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0163] S3: Add the carbon-coated lithium iron phosphate positive electrode material obtained above to a 2M NaOH aqueous solution, stir it thoroughly and then transfer it into a reactor, react at 200°C for 6 hours, cool it to room temperature after the reaction, filter it, and wash it with deionized water and anhydrous ethanol. Finally, spray granulation is used to obtain the surface hydroxylated carbon-coated lithium iron phosphate.
[0164] S4: Take an appropriate amount of sodium hydride (0.2 parts) and stir to dissolve in DMF under Ar protection, add an appropriate amount of hydroxylated carbon-coated lithium iron phosphate powder (1 part), stir and react at 40°C for 4 hours, then raise the temperature to 60°C, add an appropriate amount of chloroacetone (0.5 parts) and react for 12 hours, cool to room temperature and mature for 1 hour, stop the reaction, filter the reactant, and wash it repeatedly with deionized water and anhydrous ethanol, and finally use spray granulation to obtain a carbon-coated lithium iron phosphate positive electrode material with carbonyl groups on the surface.
[0165] (2) Electrode preparation
[0166] According to specific requirements, the positive electrode sheet and the negative electrode sheet of Example 4 are prepared according to the electrode sheet preparation method and process of Example 1.
[0167] (3) The positive electrode sheet and the negative electrode sheet obtained in Example 4 were assembled into a soft-pack battery cell according to the method of Example 1. The resulting soft-pack battery cell had a nominal capacity of 2.3 Ah.
[0168] Example 5
[0169] (1) Preparation of modified materials
[0170] S1: Weigh 1 part of lithium iron phosphate precursor iron phosphate and 1.02 parts of lithium source, add appropriate amount (2-3 parts) of anhydrous ethanol, and ball mill at 500rpm for 12h to obtain a mixed slurry with a particle size of 300-1000nm, then use spray granulation to obtain powder, place the powder in a tubular furnace, and calcine at 650℃ for 24h in Ar atmosphere to obtain lithium iron phosphate powder.
[0171] S2: Take 1 part of lithium iron phosphate powder, add 1.1 parts of glucose, add an appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500 rpm for 4 hours, spray granulate, place in a tubular furnace, and calcine at 700°C for 6 hours under Ar atmosphere to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0172] S3: Add the carbon-coated lithium iron phosphate positive electrode material obtained above into a 2M NaOH aqueous solution, stir thoroughly and move into a reactor, react at 200°C for 6 hours, cool to room temperature after the reaction, filter, and wash with deionized water and anhydrous ethanol, and finally use spray granulation to obtain surface hydroxylated carbon-coated lithium iron phosphate.
[0173] S4: Take an appropriate amount of sodium hydride (0.15 parts) and stir to dissolve in DMF under Ar protection, add an appropriate amount of hydroxylated carbon-coated lithium iron phosphate powder (1 part), stir and react at 40°C for 4 hours, then raise the temperature to 60°C, add an appropriate amount of 4-chloro-2-butanone (0.5 parts) and react for 12 hours, cool to room temperature and mature for 1 hour, stop the reaction, filter the reactant, and wash it repeatedly with deionized water and anhydrous ethanol, and finally use spray granulation to obtain a carbon-coated lithium iron phosphate positive electrode material with carbonyl groups on the surface.
[0174] (2) Electrode preparation
[0175] According to specific requirements, the positive electrode sheet and the negative electrode sheet of Example 5 are prepared according to the electrode sheet preparation method and process of Example 1.
[0176] (3) The positive electrode sheet and the negative electrode sheet obtained in Example 5 were assembled into a soft-pack battery cell according to the method of Example 1. The resulting soft-pack battery cell had a nominal capacity of 2.3 Ah.
[0177] Example 6
[0178] (1) Preparation of modified materials
[0179] S1: Weigh 1 part of lithium iron phosphate precursor iron phosphate and 1.02 parts of lithium source, add appropriate amount (2-3 parts) of anhydrous ethanol, and ball mill at 500rpm for 12h to obtain a mixed slurry with a particle size of 300-1000nm, then use spray granulation to obtain powder, place the powder in a tubular furnace, and calcine at 650℃ for 24h in Ar atmosphere to obtain lithium iron phosphate powder.
[0180] S2: Take 1 part of lithium iron phosphate powder, add 1.1 parts of glucose, add an appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500 rpm for 4 hours, spray granulate, place in a tubular furnace, and calcine at 700°C for 6 hours under Ar atmosphere to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0181] S3: Add the carbon-coated lithium iron phosphate positive electrode material obtained above to a 2M NaOH aqueous solution, stir it thoroughly and then transfer it into a reactor, react at 200°C for 6 hours, cool it to room temperature after the reaction, filter it, and wash it with deionized water and anhydrous ethanol. Finally, spray granulation is used to obtain the surface hydroxylated carbon-coated lithium iron phosphate.
[0182] S4: Take an appropriate amount of sodium hydride (0.15 parts) and stir to dissolve in DMF under Ar protection, add an appropriate amount of hydroxylated carbon-coated lithium iron phosphate powder (1 part), stir and react at 40°C for 4 hours, then raise the temperature to 60°C, add an appropriate amount of bromoacetone (0.5 parts) and react for 12 hours, cool to room temperature and mature for 1 hour, stop the reaction, filter the reactant, and wash it repeatedly with deionized water and anhydrous ethanol, and finally use spray granulation to obtain a carbon-coated lithium iron phosphate positive electrode material with carbonyl groups on the surface.
[0183] (2) Electrode preparation
[0184] According to specific requirements, the positive electrode sheet and the negative electrode sheet of Example 6 are prepared according to the electrode sheet preparation method and process of Example 1.
[0185] (3) The positive electrode sheet and the negative electrode sheet obtained in Example 6 were assembled into a soft-pack battery cell according to the method of Example 1. The resulting soft-pack battery cell had a nominal capacity of 2.3 Ah.
[0186] Example 7
[0187] (1) Preparation of modified materials
[0188] S1: Weigh 1 part of lithium iron phosphate precursor iron phosphate and 1.02 parts of lithium source, add appropriate amount (2-3 parts) of anhydrous ethanol, and ball mill at 500rpm for 12h to obtain a mixed slurry with a particle size of 300-1000nm, then use spray granulation to obtain powder, place the powder in a tubular furnace, and calcine at 650℃ for 24h in Ar atmosphere to obtain lithium iron phosphate powder.
[0189] S2: Take 1 part of lithium iron phosphate powder, add 1.1 parts of glucose, add an appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500 rpm for 4 hours, spray granulate, place in a tubular furnace, and calcine at 700°C for 6 hours under Ar atmosphere to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0190] S3: Add the carbon-coated lithium iron phosphate positive electrode material obtained above to a 2M NaOH aqueous solution, stir it thoroughly and then transfer it into a reactor, react at 200°C for 6 hours, cool it to room temperature after the reaction, filter it, and wash it with deionized water and anhydrous ethanol. Finally, spray granulation is used to obtain the surface hydroxylated carbon-coated lithium iron phosphate.
[0191] S4: Take an appropriate amount of sodium hydride (0.05-0.15 parts) and stir to dissolve in DMF under Ar protection, add an appropriate amount of hydroxylated carbon-coated lithium iron phosphate powder (1 part), stir and react at 40°C for 4 hours, then raise the temperature to 60°C, add an appropriate amount of 4-bromo-2-butanone (0.5 parts) and react for 12 hours, cool to room temperature and mature for 1 hour, stop the reaction, filter the reactant, and wash it repeatedly with deionized water and anhydrous ethanol, and finally use spray granulation to obtain a carbon-coated lithium iron phosphate positive electrode material with carbonyl groups on the surface.
[0192] (2) Electrode preparation
[0193] According to specific requirements, the positive electrode sheet and the negative electrode sheet of Example 7 are prepared according to the electrode sheet preparation method and process of Example 1.
[0194] (3) The positive electrode sheet and the negative electrode sheet obtained in Example 7 were assembled into a soft-pack battery cell according to the method of Example 1. The resulting soft-pack battery cell had a nominal capacity of 2.3 Ah.
[0195] Example 8
[0196] (1) Preparation of modified materials
[0197] S1: Weigh 1 part of lithium iron phosphate precursor iron phosphate and 1.02 parts of lithium source, add appropriate amount (2-3 parts) of anhydrous ethanol, and ball mill at 500rpm for 12h to obtain a mixed slurry with a particle size of 300-1000nm, then use spray granulation to obtain powder, place the powder in a tubular furnace, and calcine at 650℃ for 24h in Ar atmosphere to obtain lithium iron phosphate powder.
[0198] S2: Take 1 part of lithium iron phosphate powder, add 1.1 parts of glucose, add an appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500 rpm for 4 hours, spray granulate, place in a tubular furnace, and calcine at 700°C for 6 hours under Ar atmosphere to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0199] S3: Add the carbon-coated lithium iron phosphate positive electrode material obtained above to a 2M NaOH aqueous solution, stir it thoroughly and then transfer it into a reactor, react at 200°C for 6 hours, cool it to room temperature after the reaction, filter it, and wash it with deionized water and anhydrous ethanol. Finally, spray granulation is used to obtain the surface hydroxylated carbon-coated lithium iron phosphate.
[0200] S4: Take an appropriate amount of sodium hydride (0.05-0.15 parts) and stir to dissolve in DMF under Ar protection, add an appropriate amount of hydroxylated carbon-coated lithium iron phosphate powder (1 part), stir and react at 40°C for 4 hours, then raise the temperature to 60°C, add an appropriate amount of chloroacetamide (0.5 parts) and react for 12 hours, cool to room temperature and mature for 1 hour, stop the reaction, filter the reactant, and wash it repeatedly with deionized water and anhydrous ethanol, and finally use spray granulation to obtain a carbon-coated lithium iron phosphate positive electrode material with carbonyl groups on the surface.
[0201] (2) Electrode preparation
[0202] According to specific requirements, the positive electrode sheet and the negative electrode sheet of Example 8 are prepared according to the electrode sheet preparation method and process of Example 1.
[0203] (3) The positive electrode sheet and the negative electrode sheet obtained in Example 8 were assembled into a soft-pack battery cell according to the method of Example 1. The resulting soft-pack battery cell had a nominal capacity of 2.3 Ah.
[0204] Example 9
[0205] (1) Material preparation
[0206] S1: Weigh 1 part of lithium iron phosphate precursor iron phosphate and 1.02 parts of lithium source, add appropriate amount (2-3 parts) of anhydrous ethanol, and ball mill at 500rpm for 12h to obtain a mixed slurry with a particle size of 300-1000nm, then use spray granulation to obtain powder, place the powder in a tubular furnace, and calcine at 650℃ for 24h in Ar atmosphere to obtain lithium iron phosphate powder.
[0207] S2: Take 1 part of lithium iron phosphate powder, add 1.1 parts of glucose, add an appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500 rpm for 4 hours, spray granulate, place in a tubular furnace, and calcine at 700°C for 6 hours under Ar atmosphere to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0208] S3: Add the carbon-coated lithium iron phosphate positive electrode material obtained above to a 2M NaOH aqueous solution, stir it thoroughly and then transfer it into a reactor, react at 200°C for 6 hours, cool it to room temperature after the reaction, filter it, and wash it with deionized water and anhydrous ethanol. Finally, spray granulation is used to obtain the surface hydroxylated carbon-coated lithium iron phosphate.
[0209] S4: Take an appropriate amount of sodium hydride (0.05-0.15 parts) and stir to dissolve in DMF under Ar protection, add an appropriate amount of hydroxylated carbon-coated lithium iron phosphate powder (1 part), stir and react at 40°C for 4 hours, then raise the temperature to 60°C, add an appropriate amount of 3-chloropropionamide (0.5 parts) and react for 12 hours, cool to room temperature and mature for 1 hour, stop the reaction, filter the reactant, and wash it repeatedly with deionized water and anhydrous ethanol, and finally use spray granulation to obtain a carbon-coated lithium iron phosphate positive electrode material with carbonyl groups on the surface.
[0210] (2) Electrode preparation
[0211] According to specific requirements, the positive electrode sheet and the negative electrode sheet of Example 8 are prepared according to the electrode sheet preparation method and process of Example 1.
[0212] (3) The positive electrode sheet and the negative electrode sheet obtained in Example 9 were assembled into a soft-pack battery cell according to the method of Example 1. The resulting soft-pack battery cell had a nominal capacity of 2.3 Ah.
[0213] Comparative Example 1 (Carbon Coating Modification)
[0214] S1: Weigh 1 part of lithium iron phosphate precursor iron phosphate and 1.02 parts of lithium source, add appropriate amount (2-3 parts) of anhydrous ethanol, and ball mill at 500rpm for 12h to obtain a mixed slurry with a particle size of 300-1000nm, then use spray granulation to obtain powder, place the powder in a tubular furnace, and calcine at 650℃ for 24h in Ar atmosphere to obtain lithium iron phosphate powder.
[0215] S2: Take 1 part of lithium iron phosphate powder, add 1.1 parts of glucose, add an appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500 rpm for 4 hours, spray granulate, place in a tubular furnace, and calcine at 700°C for 6 hours under Ar atmosphere to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0216] (2) Electrode preparation
[0217] According to specific requirements, the positive electrode sheet and the negative electrode sheet of Comparative Example 1 were prepared according to the electrode sheet preparation method and process of Example 1.
[0218] (3) The positive electrode sheet and the negative electrode sheet obtained in Comparative Example 1 were assembled into a soft-pack battery cell according to the method of Example 1. The resulting soft-pack battery cell had a nominal capacity of 2.3 Ah.
[0219] Comparative Example 2 (Hydroxyl Modification)
[0220] S1: Weigh 1 part of lithium iron phosphate precursor iron phosphate and 1.02 parts of lithium source, add appropriate amount (2-3 parts) of anhydrous ethanol, and ball mill at 500rpm for 12h to obtain a mixed slurry with a particle size of 300-1000nm, then use spray granulation to obtain powder, place the powder in a tubular furnace, and calcine at 650℃ for 24h in Ar atmosphere to obtain lithium iron phosphate powder.
[0221] S2: Take 1 part of lithium iron phosphate powder, add 1.1 parts of glucose, add an appropriate amount (2-3 parts) of anhydrous ethanol, ball mill at 500 rpm for 4 hours, spray granulate, place in a tubular furnace, and calcine at 700°C for 6 hours under Ar atmosphere to obtain a carbon-coated lithium iron phosphate positive electrode material.
[0222] S3: Add the carbon-coated lithium iron phosphate positive electrode material obtained above into a 2M NaOH aqueous solution, stir thoroughly and move into a reactor, react at 200°C for 6 hours, cool to room temperature after the reaction, filter, and wash with deionized water and anhydrous ethanol, and finally use spray granulation to obtain surface hydroxylated carbon-coated lithium iron phosphate.
[0223] (2) Electrode preparation
[0224] According to specific requirements, the positive electrode sheet and the negative electrode sheet of Comparative Example 2 were prepared according to the electrode sheet preparation method and process of Example 1.
[0225] (3) The positive electrode sheet and the negative electrode sheet obtained in Comparative Example 2 were assembled into a soft-pack battery cell according to the method of Example 1. The resulting soft-pack battery cell had a nominal capacity of 2.3 Ah.
[0226] The wettability test of the pole pieces prepared in Examples 1 to 9 and Comparative Examples 1 to 2 was as follows:
[0227] Cut a pole piece with a size of 20 cm in length and 10 cm in width, fix one width side of the pole piece with a clamp, connect it to a weighing meter and then fix it on a rack, and immerse the other width side of the pole piece in the electrolyte with an immersion height of 1 cm. Zero the weighing meter before immersion. After the pole piece is immersed in the electrolyte, record the change of the reading of the weighing meter over time, so as to obtain the wettability of the electrolyte of each pole piece.
[0228] Test the liquid absorption of the positive electrode sheets of the positive electrode materials prepared under various experimental conditions. Figure 1 The liquid absorption curves of the positive electrode materials with different strong base ratios in each embodiment; Figure 2 Liquid absorption curve of positive electrode materials prepared with different halides.
[0229] Depend on Figure 1The results show that by changing the ratio of strong base in the carbonyl generation reaction (experiments 1-4), the positive electrode material was prepared. As the ratio of strong base increased, the liquid absorption of the prepared positive electrode material electrode gradually increased, indicating that the wettability of the positive electrode material to the electrolyte was improved. When the amount of strong base was increased to 0.15 parts, the liquid absorption of the electrode would no longer increase after the ratio of strong base was increased. This is because for reaction (1), the strong base was already in excess and all the -OH on the carbon surface had reacted. That is, when the weight ratio of the alkaline substance to the surface hydroxylated carbon-coated positive electrode active substrate was above 0.05:1, the wettability could meet the requirements. At 0.2:1, the wettability was already stable. Taking all factors into consideration, the preferred range was (0.1-0.2):1, which could fully react without destroying the material structure or wasting raw materials.
[0230] Depend on Figure 2 The results show that: Experimental Examples 3, 5, 6, and 7 use different halogenated ketones as reactants to modify the surface of the coated carbon material. From the experimental results, it can be seen that the wettability of the lithium iron phosphate material modified by chloroacetone, 4-chloro-2-butanone, bromoacetone, and 4-bromo-2-butanone in the embodiment of the present invention is significantly improved compared with the wettability of Comparative Examples 1 and 2 that do not use halogenated ketone modification, indicating that only using the carbon coating modification method of Comparative Example 1 and the hydroxyl modified carbon coating layer method of Comparative Example 2 has no obvious effect on improving the wettability of the positive electrode sheet, and the present invention significantly improves the wettability of the positive electrode active material in ester solvents by introducing lipophilic groups into the carbon coating layer.
[0231] Depend on Figure 2 The results show that the present invention improves the wettability of the positive electrode material after modification with halogenated ketones. From the curve, it can be seen that the wettability of the material after modification with chloroacetone is slightly better than that after modification with 4-chloro-2-butanone, and the wettability of the material after modification with bromoacetone is slightly better than that after modification with 4-bromo-2-butanone. The reason is that as the carbon chain increases, the electronegativity of the carbon atom connected to the halogen decreases, thereby increasing the reaction formula (2) (C) n -(ONa) n +(XC n H 2n-1 O)n→(C) n -(OC n H 2n-1 O) n At the same time, under the same carbon chain length, the wettability of the chloroketone-modified material to the electrolyte is relatively better than that of the brominated ketone. The reason is that the chlorine atom is more non-metallic than the bromine atom, which makes the carbon atom to which it is connected more electronegative, making reaction (2) easier to proceed.
[0232] For the positive electrode materials modified with halogenated amide (Example 8, Example 9), the wettability trend is the same as that of the positive electrode materials modified with halogenated ketone, and the wetting effect of the material modified with chloroacetamide is slightly better than that of 3-chloropropionamide. The wetting effect of the material modified with halogenated amide is slightly worse than that of the material modified with halogenated ketone as a whole; this is because the polarity of the amide group is large relative to the carbonyl group, and the difference in polarity with the electrolyte is greater than that of the carbonyl group, resulting in lower wettability. Even so, the wettability of the modified positive electrode materials of Examples 8 and 9 of the present invention in ester electrolytes is still significantly better than that of Comparative Examples 1 and 2. Examples 8 and 9 of the present invention use halogenated amide-modified carbon-coated lithium iron phosphate materials that have good wettability in ester electrolytes, such as chloroacetamide, chloropropionamide, chlorobutanamide, etc.
[0233] Combination Figure 2 The embodiments and comparative examples show that the wettability of the positive electrode material after being modified by halogenated ketone and halogenated amide is significantly improved compared with the wettability of the positive electrode material in the comparative example which is not modified by halogenated ketone.
[0234] Tests on the electrical properties of the soft-pack batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 2:
[0235] (1) At 25°C, the battery cells of each embodiment were charged and discharged at a power of 0.5P, with a time interval of 10 min between charging and discharging. The charge and discharge capacity and energy of the battery cells of each embodiment were recorded, and the energy efficiency was calculated; as shown in Table 1 and Figure 3 shown.
[0236] (2) At 25°C, the battery cells were charged to 10% SOC, 50% SOC, and 90% SOC, respectively, and then charged and discharged with a current of 2C for 10 seconds. The DCR internal resistance of the battery cells at different SOCs in different embodiments was calculated. Figure 4 and Figure 5 shown.
[0237] Table 1
[0238]
[0239] The experimental results show that the electrical properties of the carbon-coated surface-modified cathode material are not affected, and the energy efficiency results of the soft-packed cells obtained in different embodiments (Table 1 and Figure 3 ) and the results obtained from the electrode wettability are consistent. The better the electrode wettability, the higher the energy efficiency of the battery cell. Good wettability can reduce the internal resistance of the battery cell ( Figure 4 and Figure 5The results confirmed that the improvement in the wettability of the electrode has a significant effect on improving the performance of the battery cell), reducing the heat generated during the charging and discharging process, thereby improving the energy utilization rate. It should be noted that the terms "first", "second", etc. in the specification and claims of this application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way are interchangeable where appropriate, so that the embodiments of the present application described herein can, for example, be implemented in an order other than those described herein.
[0240] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the positive electrode sheet comprises a foil and a positive electrode slurry coated on the surface of the foil; the positive electrode slurry comprises a positive electrode material; characterized in that: The positive electrode material comprises a positive electrode active substrate, the surface of the positive electrode active substrate is coated with a carbon coating layer; the surface of the carbon coating layer has an esterophilic group, the esterophilic group is a C2-C8 carbonyl-containing group, and the structural formula of the esterophilic group is: Formula I; In Formula I, R1 is a C1-C4 alkylene group, and R2 is a C1-C4 alkyl group or an amino group; The lipophilic group is chemically bonded to the surface of the carbon coating layer in the form of a covalent bond; The electrolyte includes an ester solvent, and the ester solvent is selected from one or more of dimethyl carbonate, ethylene carbonate, methyl ethyl carbonate and diethyl carbonate.
2. The battery according to claim 1, characterized in that The weight proportion of the lipophilic group in the carbon coating layer is 1% to 2.5%; And / or, the weight of the carbon coating layer is 1-2% of the weight of the positive electrode active substrate; And / or, the positive electrode active substrate includes lithium iron phosphate, lithium manganese iron phosphate or lithium nickel iron phosphate.
3. The battery according to claim 1 or 2, characterized in that: The method for preparing the positive electrode material comprises the following steps: Step S1: obtaining a positive electrode active substrate; Step S2: performing carbon coating modification on the positive electrode active substrate to obtain a carbon coated positive electrode active substrate; Step S3: performing surface modification on the carbon-coated positive electrode active substrate, introducing esterophilic groups on the surface of the carbon coating layer, and forming the positive electrode material.
4. The battery according to claim 3, characterized in that The lipophilic group in step S3 is derived from the carbonyl group in the halogenated ketone or the carbonyl group in the halogenated amide; And / or, in step S3, the process of surface modifying the carbon-coated positive electrode active substrate includes: Step S3-1: mixing a carbon-coated positive electrode active substrate and an alkaline solution, heating the mixture for reaction, and obtaining a carbon-coated positive electrode active substrate with a hydroxylated surface; Step S3-2: mixing the surface hydroxylated carbon-coated positive electrode active substrate, an alkaline substance and a solvent in an inert atmosphere, and heating the mixture for reaction to obtain an intermediate; Step S3-3: mixing the intermediate and the compound containing the lipophilic group in an inert atmosphere, heating and reacting to obtain a carbon-coated positive electrode active substrate having the lipophilic group on the surface, i.e., the positive electrode material; Wherein, the compound containing the esterophilic group is a halogenated ketone or a halogenated amide; The halogenated ketone has a structure shown in Formula II: Formula II; In formula II, R1 is a C1-C4 alkylene group, X is a halogen atom, and R2 is a C1-C4 alkyl group; The halogenated amide has a structure shown in Formula III: Formula III; In formula III, R1 is a C1-C4 alkylene group, and X is a halogen atom.
5. The battery according to claim 4, characterized in that In step S3-2, the alkaline substance includes one or more of sodium hydride, potassium hydride, lithium diisopropylamide and lithium bistrimethylsilylamide; and / or, the solvent comprises N,N-dimethylformamide; And / or, the inert atmosphere comprises an argon atmosphere; And / or, the weight ratio of the alkaline substance to the surface hydroxylated carbon-coated positive electrode active substrate is (0.05-0.2): 1; And / or, the heating reaction conditions in step S3-2 include: temperature of 30°C to 50°C, and time of 3.5 to 4.5 h.
6. The battery according to claim 4 or 5, characterized in that: In step S3-3, the halogenated ketone is selected from one or more of chloroacetone, chlorobutyl ketone, bromoacetone, bromobutyl ketone and iodoacetone; And / or, the halogenated amide is selected from one or more of chloroacetamide, 3-chloropropionamide, and chlorobutanamide.
7. The battery according to claim 4 or 5, characterized in that: The weight ratio of the alkaline substance, the surface hydroxylated carbon-coated positive electrode active substrate and the compound containing the esterophilic group is (0.05-0.2):1:(0.4-0.6).
8. The battery according to claim 4 or 5, characterized in that: The conditions for the heating reaction in step S3-3 include: a reaction temperature of 55°C to 65°C and a reaction time of 10 to 18 hours; And / or, in the step S3-3, the product after the heating reaction is cooled to 20°C~35°C and aged for 1~2h to obtain a crude product, and the crude product is filtered, washed with water and spray granulated in sequence to obtain a carbon-coated positive electrode active substrate having the lipophilic groups on the surface, i.e., the positive electrode material.
9. The method for preparing a battery according to claim 4 or 5, characterized in that: In the step S3-1, the ratio of the carbon-coated positive electrode active substrate to the alkali solution is (20-30) g: 100 mL, and the concentration of the alkali solution is 1.5-2.5 mol / L; And / or, in step S3-1, the alkali solution is selected from one or more of a sodium hydroxide solution, a potassium hydroxide solution and a lithium hydroxide solution; And / or, the conditions of the heating reaction in step S3-1 include: temperature of 180°C to 220°C and time of 5.5 to 6.5 hours.
10. The method for preparing a battery according to claim 3, characterized in that: In the step S1, in the step S2, the carbon source for carbon coating modification includes one or more of glucose, sucrose, citric acid, polystyrene and biomass materials; And / or, in step S2, the process of carbon-coating the positive electrode active substrate comprises: mixing the positive electrode active substrate and a carbon source, and calcining in an inert atmosphere to obtain the carbon-coated positive electrode active substrate; wherein, The weight ratio of the positive electrode active substrate to the carbon source is 1:(1-1.2); The inert atmosphere includes an argon atmosphere; The calcination conditions include: a temperature of 550° C. to 650° C. and a time of 5.5 to 6.5 hours.
Citation Information
Patent Citations
Protective layer for lithium sulphur battery, preparation method thereof and lithium sulphur battery using protective layer
CN104393349A
Hydrophilic surface-modified carbonaceous particulate material
CN106660798A